2016
DOI: 10.1590/1807-1929/agriambi.v20n1p72-77
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide activity of clove essential oil on bean weevil and maize weevil

Abstract: A B S T R A C TBean weevil and maize weevil can cause considerable damage to stored grains. These insects are mainly controlled with synthetic chemical insecticides, which may bring serious problems to human and environmental health. Therefore, this study aimed to evaluate the efficiency of the essential oil of clove [Syzygium aromaticum (L.) Merrill & Perry (Myrtaceae) (origin: Bahia, season Sep.2014-Feb.2015] in the control of S. zeamais and A. obtectus under laboratory conditions. The essential oil was extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
1
20
0
5
Order By: Relevance
“…The relative percentages of components were calculated based on the total quantity of the four major components because other compounds were also present, although not in significant proportions. Despite all the factors that may interfere in the chemical composition of an essential oil, the present results corroborate the findings of other research studies carried out on clove essential oil that showed the major constituent in this oil to be eugenol (Silvestri et al ., ; Mello et al ., ; Jairoce et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The relative percentages of components were calculated based on the total quantity of the four major components because other compounds were also present, although not in significant proportions. Despite all the factors that may interfere in the chemical composition of an essential oil, the present results corroborate the findings of other research studies carried out on clove essential oil that showed the major constituent in this oil to be eugenol (Silvestri et al ., ; Mello et al ., ; Jairoce et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A CL50 para A. obtectus foi 9,45 μL g-1 contra 10,15 μL g-1 do S. zeamais. A utilização do óleo essencial de cravo-da-índia representa uma alternativa promissora a ser usada em condições de armazenagem para o manejo integrado de pragas de grãos armazenados (JAIROCE et al, 2016).…”
Section: Pesquisa Experimentalunclassified
“…However, studies focusing on the effects of extracts or metabolites on plant pests are scarce [27,28]. The toxicity of essential oils and organic extracts of Eugenia caryophyllata leaves has been reported in the human ectoparasite Pediculus capitis [29], the mosquito Aedes aegypti [30], the stored grain pests Acanthoscelides obtectus , Sitophilus zeamais , and Tribolium castaneum [31,32] and the plant feeders Oryctes agamemnon , Pochazia shantungensis , and Trialeurodes vaporariorum [33,34,35], and in the nematodes Bursaphelenchus xylophilus and Meloidogyne incognita [36]. In addition, essential oils from Eugenia uniflora have shown strong repellent effects on Diaphania hyalinata [37].…”
Section: Introductionmentioning
confidence: 99%